A modeling methodology for designing agents networks using timed hybrid Petri nets. (April 2017) - Gudiño-Mendoza, Berenice; López-Mellado, Ernesto
This paper presents a modeling methodology for designing networked agents systems. It focuses on the agent hybrid state representation, its dynamic behavior, and its interaction with neighbor agents. The agent's internal state as well as the communication interface between agents is modeled using timed hybrid Petri nets. The methodology is illustrated through the modeling of a case study related to energy interchange networks. The simulation of the case study model is included to illustrate the advantages the proposed methodology.